Non-Rigid 3D Human Models - David Pickup (19654909) (2024)
The dataset contains a collection of human models, representing a variety of individuals in a variety of poses. It includes both a dataset created from scans of real individuals, and a dataset of synthetically generated humans. The dataset has been used to benchmark non-rigid 3D shape retrieval algorithms. Results based upon these data are published at http://doi.org/10.1007/s11263-016-0903-8